1981
DOI: 10.3171/jns.1981.54.5.0677
|View full text |Cite
|
Sign up to set email alerts
|

Basilar-middle meningeal artery anastomoses associated with a cerebral aneurysm

Abstract: ~" Unique radiographic and autopsy findings are described in a patient with bilateral basilar artery-middle meningeal artery (BA-MMA) anastomoses associated with a ruptured aneurysm of the anterior communicating artery. The literature, anatomy, and embryology of BA-MMA anastomosis is reviewed.KEY WORDS 9 basilar artery 9 cerebral aneurysm 9 carotid artery 9 cerebral arteries 9 meningeal artery 9 vascular anastomosis Address reprint requests to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Various sources of anomalous origin of the MMA have been reported in the literature (Table 1). 3–12 Some authors have described the anomalous origin of the MMA from the basilar artery 2–6 . The very first case of MMA origin from basilar artery was reported by Altman in 1947 during the postmortem dissection of a 7‐month old fetus 2 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Various sources of anomalous origin of the MMA have been reported in the literature (Table 1). 3–12 Some authors have described the anomalous origin of the MMA from the basilar artery 2–6 . The very first case of MMA origin from basilar artery was reported by Altman in 1947 during the postmortem dissection of a 7‐month old fetus 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the territorial supply of the MMA is replaced, at least in part, by the basilar‐middle meningeal anastomosis. Subsequently, in 1981, Katz et al 5 described a patient with cerebral aneurysm and associated basilar‐MMA anastomosis. Most recently, Shah and Hurst 6 described an MMA originating from a large lateral pontine branch of the basilar artery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations